Perkembangan Penelitian Tipografi: Kajian Bibliometrik - Santoso, Citra Fadillah (Jurnal Bahasa Rupa, 2023)
An essential component of visual communication design is typography. Moreover, research on typography has been done in the past from both the standpoints of study and creation. Yet, there has never been research done on examining the development trend of studies on the subject of typography. Therefore, the following research questions were addressed: (1) What are the trends in research productivity regarding to typography topics based on year, publication source, affiliation, country, citation, and authorship from year to year? and (2) How is the development of research themes regarding to typography research from year to year? To conducted the research question, this research used the bibliometric method. Based on the keyword "typography" in the Scopus database, the information was retrieved, then examined and visualized using the Vos Viewer. The study's findings indicate that there has been a noticeable increase in typographic research from 1854 to 2022 in the Scopus database. Tiny nodes show up as a result of the co-occurrence visualization, indicating that there are still unique potential for research on typography-related issues. In the eight clusters, these tiny nodes are dispersed outside of the big nodes (red, green, blue, yellow, orange, brown, light blue, and purple clusters). Research possibilities with typography topics that contain the novelty can also be produced from new research that has been indexed in the Scopus database, in addition to being based on these tiny nodes.